Composition Dependence Structural and Optical Properties of Silicon Germanium (SiχGe1−χ) Thin Films - Syafiqa Nasir; Fuei, Pien Chee; Bablu Kumar Ghosh; Muhammad Izzuddin Rumaling; Rosfayanti Rasmidi; Mivolil Duinong; Floressy Juhim (MDPI, 2023)
This study investigates the structural and optical characteristics of Silicon Germanium (SiGe) thin films with varying compositions and annealing temperatures for potential use in electronic and optoelectronic devices. Si0.8Ge0.2 and Si0.9Ge0.1 films were deposited onto a high-temperature quartz substrate and annealed at 600 °C, 700 °C, and 800 °C before being evaluated using an X-Ray Diffractometer (XRD), Atomic Force Microscopy (AFM), and a UV-Vis Spectrometer for structural and optical properties. The results show that increasing the annealing temperature results in an increase in crystalline size for both compositions. The transmittance for Si0.8Ge0.2 decreases slightly with increasing temperature, while Si0.9Ge0.1 remains constant. The optical band gap for Si0.9Ge0.1 thin film is 5.43 eV at 800 °C, while Si0.8Ge0.2 thin film is 5.6 eV at the same annealing temperature. XRD data and surface analysis reveal significant differences between the band edges of SiGe nano-structure materials and bulk crystals. However, the possibility of a SiGe nano-crystal large band gap requires further investigation based on our study and related research works.